Faktor-Faktor Yang Mempengaruhi Auditor Switching Pada Perusahaan Trade and Services Yang Terdaftar di BEI 2017-2021 - Rona Chyta Silalahi; Valentine Siagian (Journal of Economic, Bussines and Accounting (COSTING), 2022)
The independence of an external auditor can be maintained by continuously changing auditors in accordance with applicable government regulations. This study aims to test the CEO turnover, audit committee characteristics, financial distress, KAP reputation, audit opinion and audit delay on auditor switching. This study uses secondary data on trade and services companies listed on the Indonesia Stock Exchange in 2017-2021. This study used a purposive sampling technique which resulted in 335 sample observations from 67 total companies in accordance with the provisions made by the author. Hypothesis testing in this study used logistic regression. The data has been processed using SPSS version 23 and shows the results that CEO turnover has a significant effect on auditor switching and the characteristics of the audit committee, financial distress, KAP reputation, audit opinion and audit delay have no significant effect on auditor switching. Keywords: CEO Turnover, Audit Committee Characteristics, Financial Distress, KAP Reputation, Audit Opinions, Audit Delay